Estimating the proportion of Medicaid-eligible pregnant women in Louisiana who do not get abortions when Medicaid does not cover abortion - Sarah C. M. Roberts; Nicole E. Johns; Valerie Williams; Erin Wingo; Ushma D. Upadhyay (BMC, 2019)
Abstract Background To estimate the proportion of pregnant women in Louisiana who do not obtain abortions because Medicaid does not cover abortion. Methods Two hundred sixty nine women presenting at first prenatal visits in Southern Louisiana, 2015-2017, completed self-administered iPad surveys and structured interviews. Women reporting having considered abortion were asked whether Medicaid not paying for abortion was a reason they had not had an abortion. Using study data and published estimates of births, abortions, and Medicaid-covered births in Louisiana, we projected the proportion of Medicaid births that would instead be abortions if Medicaid covered abortion in Louisiana. Results 28% considered abortion. Among women with Medicaid, 7.2% [95% CI 4.1-12.3] reported Medicaid not paying as a reason they did not have an abortion. Existing estimates suggest 10% of Louisiana pregnancies end in abortion. If Medicaid covered abortion, this would increase to 14% [95% CI 12, 16]. 29% [95% CI 19, 41] of Medicaid eligible pregnant women who would have an abortion with Medicaid coverage, instead give birth. Conclusions For a substantial proportion of pregnant women in Louisiana, the lack of Medicaid funding remains an insurmountable barrier to obtaining an abortion. Forty years after the Hyde Amendment was passed, lack of Medicaid funding for abortion continues to have substantial impacts on women's ability to obtain abortions.